Demographic and Food Insecurity Factors Linked to Adolescent Overweight in Thailand: A Binary Logistic Regression Analysis - Nugroho, Purwo Setiyo; Abbani, Abubakar Yakubu (JPKM: Jurnal Profesi Kesehatan Masyarakat, 2026)
Overweight among adolescents in Thailand is a growing public health concern, influenced by demographic and socioeconomic factors. Food insecurity further complicates this issue through the food insecurity–obesity paradox, where limited access to nutritious food coexists with excess weight. However, nationally representative evidence on this relationship remains limited. This study examined the association between demographic characteristics (sex, age, and school grade) and food insecurity with overweight among Thai adolescents using data from the 2021 Global School-based Student Health Survey (GSHS). This study employed a cross-sectional design using secondary data. A total of 4,510 students aged 13–17 years were included, with an overall overweight prevalence of 19.07%. Logistic regression showed that boys had lower odds of overweight than girls (OR = 0.709, 95% CI: 0.705–0.714). Age was significantly associated with overweight, with the highest risk observed among adolescents aged 15–16 years (OR = 1.972 and 2.202). Lower school grades were associated with reduced odds compared to grade 12. Food insecurity was positively associated with overweight (OR = 1.509, 95% CI: 1.480–1.537). These findings highlight the complex interplay of demographic and contextual factors. Targeted interventions addressing age, gender, school level, and food insecurity are essential to reduce adolescent overweight in Thailand.